Enzymatic recovery of polyester building blocks from polymer blends. (August 2017) - Gamerith, Caroline; Zartl, Barbara; Pellis, Alessandro; Guillamot, Frédérique; Marty, Alain; Acero, Enrique Herrero; Guebitz, Georg M.
Graphical abstract: Highlights: Thc_Cut1 hydrolyzes PET in polymer blends without prior separation. Significant inhibitory effect of soluble released products is detectable. Main process influencing factors are particle size, temperature & enzyme stability. Abstract: In this study we investigated the ability of a cutinase from Thermobifida cellulosilytica (Thc_Cut1) to hydrolyze poly (ethylene terephthalate) (PET) moieties in different polymer blends. The composition of various materials including commercial available bottles and packaging was determined using Fourier Transform InfraRed spectroscopy (FT-IR) and Differential Scanning Calorimetry (DSC). When incubated with PET blended with polyethylene (PE) or polyamide (PA) from packaging and bottles without prior separation, Thc_Cut1 selectively hydrolyzed the PET moieties releasing terephthalic acid (TPA) and mono(2-hydroxyethyl) terephthalate (MHET). Polymer blends were hydrolyzed in an up to 9 times higher extent compared to higher crystalline pure PET. The influence of various parameters like temperature, particle size, crystallinity and product inhibition on hydrolysis of PET moieties by Thc_Cut1 was investigated. The amount of products released was up to 10 times higher when the incubation temperature was increased from 40 °C to 60 °C. The smaller the particle size the higher the hydrolysis rates were. Interestingly, semi-crystalline (24%) PET from bottles was hydrolyzed faster than powder from amorphous PET films (12%). An inhibitory effect of bis(2-hydroxyethyl) terephthalate (BHET) on hydrolysis of PET by Thc_Cut1 was observed.